(untitled) (Andamios, Revista de Investigación Social, 2015)
This paper debates the traditional notions of political transnationalism used in the United States by showing the formation and the activist process followed by the #YoSoy132 movement in New York City. The conclusion drawn is that immigrants organizations in the US have diversified their acting repertories, political perspective and their demands. Therefore, it is necessary to broaden the concept of political transnationalism to a social-political perspective. The latter will allow having a wider theoretical notion to analyze a larger number of immigrants organizations in the US.